2014
DOI: 10.1002/jcph.360
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem in children receiving continuous renal replacement therapy: Clinical trial simulations using realistic covariates

Abstract: Meropenem is frequently prescribed in children receiving continuous renal replacement therapy (CRRT). Fluid overload is often present in critically ill children and affects drug disposition. The purpose of this study was to develop a pharmacokinetic model to (1) evaluate target attainment of meropenem dosing regimens against P. aeruginosa in children receiving CRRT and (2) estimate the effect of fluid overload on target attainment. Clinical trial simulations were employed to evaluate target attainment of merop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
1
21
2
Order By: Relevance
“…[21][22][23][24][25][26][27] The standard meropenem dose in a patient this age is 20 mg/kg per dose IV every 8 to 12 hours. Further, Nehus et al 28 conducted clinical trial simulations to determine dosing regimens in children that would provide for a target attainment of 40% and 75% time above the MIC. Simulations suggested that a dosing regimen of 20 mg/kg per dose IV every 8 hours would be sufficient to obtain the aforementioned target attainments for children younger than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27] The standard meropenem dose in a patient this age is 20 mg/kg per dose IV every 8 to 12 hours. Further, Nehus et al 28 conducted clinical trial simulations to determine dosing regimens in children that would provide for a target attainment of 40% and 75% time above the MIC. Simulations suggested that a dosing regimen of 20 mg/kg per dose IV every 8 hours would be sufficient to obtain the aforementioned target attainments for children younger than 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some dialysis membranes can adsorb drugs in hemofiltration [97]. Previous studies have shown that the PK of meropenem and ticarcillin were altered in critically ill children supported with CRRT [99,100]. …”
Section: Effect Of Critical Illness On Pharmacokineticsmentioning
confidence: 99%
“…Meropenem has also been studied in children with CRRT and ECMO [99,129]. Peak meropenem concentrations were decreased in children receiving CRRT with fluid overload by an average of 6.1% in patients with 10% fluid overload, 11.5% with 20% fluid overload, and 16% with 30% fluid overload [99]. However, fluid overload did not affect CL or the target attainment of 40% and 75% time above the minimum inhibitory concentration (4 mg/mL) [99].…”
Section: Pharmacokinetic Studies In Critically Ill Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, in silico trials using Monte Carlo simulation (MCS) have been used to determine optimal drug regimens during drug discovery and development. This approach has been employed to predict optimal antibiotic doses in patients with IHD and CRRT [12,13], but not with PIRRT. Antibiotic dosing in patients with PIRRT is challenging, because dosing must take into account the pharmacokinetics altered not only by critical illness and but also by the timing of PIRRT and its associated drug clearance in relation to drug administration [14].…”
Section: Introductionmentioning
confidence: 99%